WT1 facilitates the self-renewal of leukemia-initiating cells through the upregulation of BCL2L2: WT1-BCL2L2 axis as a new acute myeloid leukemia therapy target - Zhou, Bin (J Transl Med, 2020)
BACKGROUND: Overexpression of Wilms’ tumor-1 (WT1) transcription factor facilitates proliferation in acute myeloid leukemia (AML). However, whether WT1 is enriched in the leukemia-initiating cells (LICs) and leukemia stem cells (LSCs) and facilitates the self-renewal of LSCs remains poorly understood. METHODS: MLL-AF9-induced murine leukemia model was used to evaluate the effect of knockdown of wt1 on the self-renewal ability of LSC. RNA sequencing was performed on WT1-overexpressing cells to select WT1 targets. Apoptosis and colony formation assays were used to assess the anti-leukemic potential of a deubiquitinase inhibitor WP1130. Furthermore, NOD/SCID-IL2Rγ (NSG) AML xenotransplantation and MLL-AF9-induced murine leukemia models were used to evaluate the anti-leukemogenic potential of WP1130 in vivo. RESULTS: We found that wt1 is highly expressed in LICs and LSCs and facilitates the maintenance of leukemia in a murine MLL-AF9-induced model of AML. WT1 enhanced the self-renewal of LSC by increasing the expression of BCL2L2, a member of B cell lymphoma 2 (BCL2) family, by direct binding to its promoter region. Loss of WT1 impaired self-renewal ability in LSC and delayed the progression of leukemia. WP1130 was found to modify the WT1-BCL2L2 axis, and WP1130-induced anti-leukemic activity was mediated by ubiquitin proteasome-mediated destruction of WT1 protein. WP1130 induced apoptosis and decreased colony formation abilities of leukemia cells and prolonged the overall survival in the THP1-based xenograft NSG mouse model. WP1130 also decreased the frequency of LSC and prolonged the overall survival in MLL-AF9-induced murine leukemia model. Mechanistically, WP1130 induced the degradation of WT1 by positively affecting the ubiquitination of WT1 protein. CONCLUSIONS: Our results indicate that WT1 is required for the development of AML. WP1130 exhibits anti-leukemic activity by inhibiting the WT1-BCL2L2 axis, which may represent a new acute myeloid leukemia therapy target.